Environmental risk factors for self-harm during imprisonment: a prospective cohort study - Stephenson, T; Harris, I; Armstrong, C; Fazel, S; Short, R; Blackwood, N (2024)
Introduction Self-harm is a major public health issue in the imprisoned population. Limited high-quality evidence exists for the potential impact of prison environmental factors such as solitary confinement. This pilot prospective cohort study in a large male remand prison in England sought to estimate effect sizes of a comprehensive range of prison environmental factors on self-harming behaviours. Methods A random sample of all prisoners (N=149) starting a period of imprisonment at the study prison took part in a clinical research interview, which assessed a range of known risk factors for self-harm in prison. Information concerning environmental factors, including staff numbers, cell placement and movements, and engagement in work and activities were collected from prison records. Incidents of self-harm behaviour in the 3 months after entering prison were measured using medical records and self-report at end of follow-up. Multivariable logistic regression models were calculated individually for each predictor. Results Single cell placement (OR 4.31, 95% CI 1.06-18.24, p=0.041) and more frequent cellmate (OR 1.52, CI 1.14-2.17, p=0.009) and cell (OR 1.83, 95% CI 1.28-2.86, p=0.003) changes were associated with an increased risk of self-harming behaviour. Unexpectedly, a lower staff-to-prisoner ratio (OR 0.89, CI 0.78-0.99, p=0.039) was also associated with an increased risk of self-harming behaviour. Following sensitivity analyses, the associations between frequent cell changes and self-harm behaviour, and between single cell placement and self-harm ideation, remained statistically significant. Discussion This pilot study provides prospective longitudinal data regarding relationships between prison environmental factors and self-harm behaviour. Findings regarding single cell accommodation and frequent cell changes are consistent with the prior evidence base largely derived from case-control study data. The finding regarding frequent cellmate changes predicting self-harm is novel. Findings regarding staff-prisoner ratio and self-harm most likely reflect a reverse causal relationship. Replication in larger cohort studies is required to address the limitations of this pilot study.